The root zone of graminoids: A niche for H2-consuming acetogens in a minerotrophic peatland - Meier, Anja B.; Oppermann, Sindy; Drake, Harold L.; Schmidt, Oliver (Frontiers in Microbiology, 2022)
The importance of acetogens for H2 turnover and overall anaerobic degradation in peatlands remains elusive. In the well-studied minerotrophic peatland fen Schlöppnerbrunnen, H2-consuming acetogens are conceptualized to be largely outcompeted by iron reducers, sulfate reducers, and hydrogenotrophic methanogens in bulk peat soil. However, in root zones of graminoids, fermenters thriving on rhizodeposits and root litter might temporarily provide sufficient H2 for acetogens. In the present study, root-free peat soils from around the roots of Molinia caerulea and Carex rostrata (i.e., two graminoids common in fen Schlöpnnerbrunnen) were anoxically incubated with or without supplemental H2 to simulate conditions of high and low H2 availability in the fen. In unsupplemented soil treatments, H2 concentrations were largely below the detection limit (~10 ppmV) and possibly too low for acetogens and methanogens, an assumption supported by the finding that neither acetate nor methane substantially accumulated. In the presence of supplemental H2, acetate accumulation exceeded CH4 accumulation in Molinia soil whereas acetate and methane accumulated equally in Carex soil. However, reductant recoveries indicated that initially, additional unknown processes were involved either in H2 consumption or the consumption of acetate produced by H2-consuming acetogens. 16S rRNA and 16S rRNA gene analyses revealed that potential acetogens (Clostridium, Holophagaceae), methanogens (Methanocellales, Methanobacterium), iron reducers (Geobacter), and physiologically uncharacterized phylotypes (Acidobacteria, Actinobacteria, Bacteroidetes) were stimulated by supplemental H2 in soil treatments. Phylotypes closely related to clostridial acetogens were also active in soil-free Molinia and Carex root treatments with or without supplemental H2. Due to pronounced fermentation activities, H2 consumption was less obvious in root treatments, and acetogens likely thrived on root organic carbon and fermentation products (e.g., ethanol) in addition to H2. Collectively, the data highlighted that in fen Schlöppnerbrunnen, acetogens are associated to graminoid roots and inhabit the peat soil around the roots, where they have to compete for H2 with methanogens and iron reducers. Furthermore, the study underscored that the metabolically flexible acetogens do not rely on H2, potentially a key advantage over other H2 consumers under the highly dynamic conditions characteristic for the root-zones of graminoids in peatlands.